2022
DOI: 10.3390/biomedicines10092169
|View full text |Cite
|
Sign up to set email alerts
|

The Post-Translational Modification Networking in WNK-Centric Hypertension Regulation and Electrolyte Homeostasis

Abstract: The with-no-lysine (WNK) kinase family, comprising four serine-threonine protein kinases (WNK1-4), were first linked to hypertension due to their mutations in association with pseudohypoaldosteronism type II (PHAII). WNK kinases regulate crucial blood pressure regulators, SPAK/OSR1, to mediate the post-translational modifications (PTMs) of their downstream ion channel substrates, such as sodium chloride co-transporter (NCC), epithelial sodium chloride (ENaC), renal outer medullary potassium channel (ROMK), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 261 publications
0
5
0
Order By: Relevance
“…In addition to the commonly reported characteristics of GS such as familial hyperkalemia, mild metabolic acidosis, and low PR activity with normal PA levels, our patients with the p.Glu630Gly variant of WNK1 showed hypertension (with superimposed pre-eclampsia in two cases), short stature and low weight in adults, and initial isolate hyperkalemia in one of the children. One wide-range gene panel of next-generation sequencing in nephropathies will be very useful for differential diagnosis and categorizing subgroups of patients with inherited nephropathies, including individuals with GS; this fact may help to allow the discovery of new molecular pathways that regulate blood pressure and electrolyte homeostasis, and the development of new drug targets for treatment, as has been previously suggested [29].…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the commonly reported characteristics of GS such as familial hyperkalemia, mild metabolic acidosis, and low PR activity with normal PA levels, our patients with the p.Glu630Gly variant of WNK1 showed hypertension (with superimposed pre-eclampsia in two cases), short stature and low weight in adults, and initial isolate hyperkalemia in one of the children. One wide-range gene panel of next-generation sequencing in nephropathies will be very useful for differential diagnosis and categorizing subgroups of patients with inherited nephropathies, including individuals with GS; this fact may help to allow the discovery of new molecular pathways that regulate blood pressure and electrolyte homeostasis, and the development of new drug targets for treatment, as has been previously suggested [29].…”
Section: Discussionmentioning
confidence: 92%
“…The mechanism by which UMOD has been shown to affect blood pressure is mainly the combination of TAL and DCT to modulate the activity of ion transport proteins in epithelial cells, including the renal outer medullary potassium channel (ROMK) ( 57 , 58 ), epithelial sodium channel (ENaC) ( 59 ), NKCC2 ( 60 ), and NCC ( 8 , 61 , 62 ), of which NKCC2 and NCC are the major transport proteins responsible for sodium reabsorption ( 63 ). Mutations in NKCC2 and malfunctions in its regulators are known to cause Bartter syndrome, a salt-depleting hypotensive disorder with reduced levels of UMOD, in addition to a significant reduction in NKCC2 phosphorylation in Umod(-/-) mice, where NKCC2 expression is not as strong as in WT mice, and conversely, mice with overexpressed UMOD exhibit salt-sensitive hypertension ( 64 66 ). Earlier studies confirmed that uromodulin promotes the activation of NKCC2 in a chloride-sensitive manner ( 66 ), but did not identify a specific mechanistic process for its activation, and similar to NKCC2, uromodulin also activates NCC in the DCT ( 67 ).…”
Section: Relationship Between Uromodulin and Various Cardiovascular D...mentioning
confidence: 99%
“…Mutations in NKCC2 and malfunctions in its regulators are known to cause Bartter syndrome, a salt-depleting hypotensive disorder with reduced levels of UMOD, in addition to a significant reduction in NKCC2 phosphorylation in Umod(-/-) mice, where NKCC2 expression is not as strong as in WT mice, and conversely, mice with overexpressed UMOD exhibit salt-sensitive hypertension ( 64 66 ). Earlier studies confirmed that uromodulin promotes the activation of NKCC2 in a chloride-sensitive manner ( 66 ), but did not identify a specific mechanistic process for its activation, and similar to NKCC2, uromodulin also activates NCC in the DCT ( 67 ). It was subsequently demonstrated in a growing number of animal studies that uromodulin induces a significant increase in NKCC2 and NCC phosphorylation and its activity, leading to the up-regulation of NKCC2 and NCC through the regulation of the SPS1-associated proline/alanine-rich kinase/oxidative stress-responsive kinase 1 (SPAK-OSR1) ( 55 , 66 70 ), which are involved in the pathogenesis of salt-sensitive hypertension ( 71 75 ).…”
Section: Relationship Between Uromodulin and Various Cardiovascular D...mentioning
confidence: 99%
See 2 more Smart Citations